2008
DOI: 10.1007/s10935-008-0134-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Parenting Practices of At-risk Mothers

Abstract: This study evaluated the effectiveness of an intervention designed to improve early parenting by increasing understanding of infant developmental needs and promoting maternal responsiveness as indicated by increased positive behavior support for infants and decreased psychological control. At-risk mothers were randomly assigned to control or treatment conditions, the latter consisting of training in parental responsiveness, developmental knowledge, and loving touch. Following the intervention, treatment mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 37 publications
1
23
0
12
Order By: Relevance
“…Substantial research has documented the efficacy of brief behavioral interventions for increasing empathic behaviors in diverse samples including among romantic partners (Block-Lerner, Adair, Plumb, Rhatigan & Orsillo, 2007), health care providers (Heuberger, 2010), child welfare workers (Mullins, 2011), male parolees (Marlow, Nyamanthi, Grajeda, Bailey, Weber, & Younger, 2012), and prison inmates (Palusci, Crum, Bliss & Bavolek, 2008). Furthermore, brief training interventions aimed at increasing parents’ empathy towards their children have been shown to reduce harmful parenting practices and improve parent-child relationships (Akai et al, 2008; Stolk, et al, 2008; Suchman et al, 2008; Edwards, Sullivan, Meany-Walen & Kantor, 2010; Kendrick, Mulvaney, Stevens, Mytton & Stewart-Brown, 2013). Thus, the application of targeted interventions that increase empathy for fetal well-being among smokers during pregnancy may increase their chances of quitting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial research has documented the efficacy of brief behavioral interventions for increasing empathic behaviors in diverse samples including among romantic partners (Block-Lerner, Adair, Plumb, Rhatigan & Orsillo, 2007), health care providers (Heuberger, 2010), child welfare workers (Mullins, 2011), male parolees (Marlow, Nyamanthi, Grajeda, Bailey, Weber, & Younger, 2012), and prison inmates (Palusci, Crum, Bliss & Bavolek, 2008). Furthermore, brief training interventions aimed at increasing parents’ empathy towards their children have been shown to reduce harmful parenting practices and improve parent-child relationships (Akai et al, 2008; Stolk, et al, 2008; Suchman et al, 2008; Edwards, Sullivan, Meany-Walen & Kantor, 2010; Kendrick, Mulvaney, Stevens, Mytton & Stewart-Brown, 2013). Thus, the application of targeted interventions that increase empathy for fetal well-being among smokers during pregnancy may increase their chances of quitting.…”
Section: Discussionmentioning
confidence: 99%
“…If confirmed, increasing maternal-fetal attachment during pregnancy may improve chances of smoking cessation, thereby optimizing the short and long term health of both mothers and their children (Akai et al, 2008; Suchman, DeCoste, Castiglioni, Legow & Mayes, 2008). To elucidate how modifiable maternal psychological factors related to prenatal smoking exposure may influence child outcomes, we secondarily explored how attachment may differ between non-smokers and pregnancy quitters, and by intrauterine smoking exposure status (non-smokers and pregnancy quitters versus persistent smokers).…”
Section: Introductionmentioning
confidence: 99%
“…This approach was designed to harness both the existing advantages of an established evidence-based intervention and the unique delivery advantages that may be possible via the Internet as described above. We selected this particular intervention based on several considerations (see Feil et al, 2008), which included the following: (a) it has demonstrated effectiveness in increasing sensitive and responsive parenting behaviors as well as in improving child social-emotional behavior and developmental outcomes (Landry, et al 2008; Akai, et al, 2008); (b) it makes use of educational and therapeutic strategies that have been shown consistently to promote behavioral effectiveness, including skills instruction and direct coaching of behavioral skills, active engagement of parents in personal behavior reflection, and between-session skills practice (see Kaminski. Valle, Filene, & Boyle, 2007); and (c) Intervention and assessment materials were developed and available, including parent training videos, highly detailed and specific coaching guides for session content, measures of implementation fidelity, parent engagement, parent knowledge acquisition, parent responsiveness and child behavioral engagement based on direct observation were developed and available (Feil et al, 2008).…”
Section: Technologies For Expanding the Reach Of Evidence-based Intermentioning
confidence: 99%
“…This set of information permitted personalizing the psycho-educative intervention, with modules focused on the marital role (stress management, couple's sexuality and communication skills) and the parental role (infant's sensory competences, responsiveness and construction of safe bonding, prevention of mistreatment and resilience). This differs form most studies published in the area (Akai et al, 2008;Deyo et al, 2008;Shute & Judge, 2005), which are only focused on the parenthood dimension.…”
Section: Needs Assessmentmentioning
confidence: 66%
“…This range comprises interventions at health centers, homes and in hospitals, before and/or after the infant's birth, in groups or through home visits. A large part of these studies adopts experimental or quasi-experimental designs, with pre and post-test assessments and a psycho-educative approach focused on the parenthood (Akai, Guttentag, Baggett, & Noria, 2008;Deyo, Skybo, & Carrol, 2008;Shute & Judge, 2005) or conjugality dimension (Hawkins, Fawcett, Carroll, & Gilliland, 2006), or less frequently on both (Doherty, Erickson, & LaRossa, 2006). The analysis of this literature shows that contents focused on parenthood include parental responsiveness training, children's developmental capabilities, parenting skills and newborn care.…”
mentioning
confidence: 99%